1988
DOI: 10.1093/eurheartj/9.7.782
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous balloon valvuloplasty for calcific aortic stenosis. A treatment 'sine cure'?

Abstract: Twenty-five elderly patients with calcific aortic stenosis, 12 male (48%) and 13 female (52%), mean age 74.8 +/- 7.6 years, underwent percutaneous aortic balloon valvuloplasty between March 1986 and September 1987. Twenty-two patients (88%) were in class III-IV of the New York Heart Association, 13 (52%) had a history of previous angina and 7 (28%) of syncopal attacks. All patients had been considered either unsuitable or high-risk candidates for aortic-valve replacement because of age or associated diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…In our series, we found that of the 48 patients who required a permanent pacemaker, 22 patients experienced AV block during the procedure. The possible mechanisms involved include inflammation, edema, ischemia, and mechanical trauma over the interventricular septum, with the resulting consequences in the conduction system, which may be transitory as occurs with the balloon used to predilate the native valve (19). GutiĂ©rrez et al (20) reported transitory ECG changes after implanting the Edwards-Sapien prosthesis, with the incidence of LBBB increasing from 9% at baseline to 27% after the procedure, and then falling at 1 month to 13%.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, we found that of the 48 patients who required a permanent pacemaker, 22 patients experienced AV block during the procedure. The possible mechanisms involved include inflammation, edema, ischemia, and mechanical trauma over the interventricular septum, with the resulting consequences in the conduction system, which may be transitory as occurs with the balloon used to predilate the native valve (19). GutiĂ©rrez et al (20) reported transitory ECG changes after implanting the Edwards-Sapien prosthesis, with the incidence of LBBB increasing from 9% at baseline to 27% after the procedure, and then falling at 1 month to 13%.…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, adverse events have been well recognized as associated with BAV as a stand-alone treatment [29][30][31]. Whether similar rates of complications have to be expected when performing preparatory BAV prior to TAVI remains unclear since clinical sequelae often become apparent only during the further course of the patient making discrimination of causal relation difficult.…”
Section: Main Findingsmentioning
confidence: 99%
“…Allerdings wurde das Verfahren seinerzeit wegen der hohen prozedurbedingten Komplikationsrate [8,19,45,48,54] und der hohen Restenoserate [36,42,43] innerhalb von 6-12 Monaten als auf Risikopatienten, die nicht operativ versorgt werden konnten oder im kardiogenen Schock waren, beschrĂ€nkt angesehen und in den folgenden Jahren kaum noch angewandt.…”
Section: Aortenklappenvalvuloplastieunclassified